Spanish Cinema of the 2010s: Back to Punk and Other Lessons from the Crisis. (2nd January 2019) - Triana-Toribio, Núria
Abstract: This article focuses on how Spanish cinema production has echoed the neoliberal Eurozone crisis of 2008 in mainstream (large- and medium-size productions), and in its 'opposite' the independent sector, and how the effects of the crisis can be glimpsed (within the independent sector) on music (mostly Punk) documentaries which are not ostensibly about the economy, current politics or even the present. I suggest a course through the different ways in which Spanish cinema has been touched by the crisis: through the films of 'crisis cinema' to those that focus on the 1980s and early 1990s and its youth-led and Punk-inspired musical revolutions, via films whose strategy is to address the 2008–17 period in an indirect manner, or to retreat to the pre-2008 past. My ultimate aim is to prove that this seismic change to Spain's society has forced a re-engagement with the present and the past.